Dental caries experience and determinants in young adults of the Northern State Medical University, Arkhangelsk, North-West Russia: a cross-sectional study - Drachev, Sergei; Brenn, Tormod; Trovik, Tordis A (BMC Oral Health, 2017)
Source at: https://doi.org/10.1186/s12903-017-0426-x Background - Little information exists about the experience of and risk factors for dental caries in young adults in Russia. We investigated dental caries experience and determinants in medical and dental students in North-West Russia. Methods - This cross-sectional study included 442 medical and 309 dental undergraduate students of Russian nationality aged 18–25 years from the Northern State Medical University, Arkhangelsk, Russia. Information on socio-demographic factors and oral health behaviour (regularity of dental visits, frequency of tooth-brushing, using toothpaste with fluoride, and skipping tooth-brushing) was obtained from a structured, self-administered questionnaire. Dental caries experience was based on the decayed (D) missing (M) filled (F) teeth (T) index and the Significant Caries (SiC) index, which were assessed through dental examination. Students with a DMFT index ≥9 were placed in the SiC group. Negative binomial hurdle and multivariable binary logistic regressions were used for statistical analyses. Results - The prevalence of dental caries (DMFT >0) was 96.0%, overall mean DMFT index was 7.58 (DT: 0.61, MT: 0.12, and FT: 6.84), and the corresponding SiC index was 12.50. Age 21–25 years (incidence rate ratio [IRR] = 1.09, 95% confidence interval [CI]: 1.01–1.18), being a female (IRR = 1.10, 95% CI: 1.01–1.20), high subjective socioeconomic status (SES) [IRR = 1. 11, 95% CI: 1.02–1.21], and skipping tooth-brushing (IRR = 1.09, 95% CI: 1.00–1.19) were associated with a higher DMFT index. DMFT index also increased among students who reported regular dental visits (IRR = 1.22, 95% CI: 1.10–1.36), but their odds of being in the dental caries-free group decreased (odds ratio [OR] = 0.38, 95% CI: 0.18–0.82). Significant predictors of being categorised to the SiC group were older age (OR = 1.41, 95% CI: 1.03–1.92), high subjective SES (OR = 1.57, 95% CI: 1.13–2.19), and regular dental visits (OR = 2.34, 95% CI: 1.56–3.51). Conclusions - A ...